Influence of hydrogen peroxide concentration on the detoxification of cyanide mine tailings (SCIÉNDO INGENIUM, 2023)
This research aims to compare two treatments for detoxification of cyanide mine tailings using hydrogen peroxide, the first one with a concentration of 50% and the second one with a concentration of 70%. The statistical tool ANOVA was used, together with the tukey method, to determine the differences and similarities of both treatments. The study was carried out in two trains composed of five tanks each, the treatment was randomized (DCA) for a period of 21 hours, obtaining a cyanide sample from each tank every hour. The results showed that the 70% peroxide treatment provides higher cyanide removal (
Keywords: ANOVA; effluent treatment; mining industry; chemical treatment; cyanide